Sanksi Pidana Perdagangan Perempuan (Women Trafficking) (Studi Komparatif antara Undang-Undang No. 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang dan Hukum Islam) - Zaman, Q. (JURNAL AT-TURAS, 2018)
The phenomenon of trafficking in women (women trafficking) is like an "iceberg phenomenon". Women who essentially have a high position and a great influence on family life, society and state are often used as the dominant object of the trafficking in persons. The modus operandi also varies, ranging from exploitation of violence such as being employed as sex workers (online or ordinary), cyber crime, marriages with foreign men for the purpose of drug exploitation and distribution, matchmaking agencies that are judged to be sharia, and marriage service providers siri (the case of the siri.com marriage website), and even the trafficking of women with the umroh modus operandi. Therefore it is interesting to examine how criminal sanctions are against traffickers of trafficking in women (women trafficking) with a comparative analysis between UU No. 21/2007 concerning TPPU and Islamic Law. From the results of literature analysis found that criminal sanctions in UU No. 21/2007 concerning TPPO which is a lex specialis in the case of good trafficking conducted by individuals, state administrators and corporations / organizations in line with Islamic criminal law which classifies trafficking in women as jarimah ta'zir in which the application of sanctions (uqubah) is submitted in full in the decision of the judge/ruler (uli al-amr). The necessary stay is then, the implementation is serious, firm and consistent, especially by law enforcement.